Interpretation of results of music-creative characteristics of children of pre-school age in China by suzuki-method - Цзінцю, Сунь (Scientific notes of the pedagogical department, 2019)
The author proposes an interpretation of the results of the formation of musical and creative abilities of preschool children in China by means of the Suzuki method. At the stage of the pedagogical experiment it was determined quantitative and qualitative analysis of the levels of formation of musical and creative abilities in children of preschool age in the People's Republic of China. For reliable data, methods, interviews, children's observation at musical classes, children's wounds, holidays, questionnaire surveys of music directors and parents were used. The author outlines the criteria, indicators and levels of formation of musical and creative abilities in preschool children in the People's Republic of China. On the basis of qualitative and quantitative analysis of the received diagnostic data, a methodology of the forming stage of the pedagogical experiment was developed. For its conduct, two groups of children (230 persons) were formed - experimental (EG), in which classes were conducted according to the experimental methodology and control (KG), which continued classes according to the traditional program. The introduction of the Suzuki method was aimed at the formation of musical and creative abilities of children, since Sh. Suzuki proved that human talent and abilities are not innate, but acquired because each person has the potential. The formative stage of the pedagogical experiment was carried out in such a way that the Suzuki method was implemented in practice at the following stages: adaptive-motivational, reproductive-informative, creative-activity. As a result of the pedagogical experiment, there was a progressive dynamics of changes in all levels of the formation of musical and creative abilities of preschool children in the People's Republic of China, using the Suzuki method. Prospects for further scientific research may be the introduction of the Suzuki method in the educational process of preschool institutions in Ukraine for the development of musical and creative abilities of children.